Strategic Management for Improving Education Quality at Al Irsyad Al Islamiyyah 01 Elementary School, Bandung - Ayu , Rini (The International Journal of Education Management and Sociology, 2024)
This study aims to analyze the implementation of strategic management in strategic planning, execution, and evaluation to improve educational quality. This qualitative descriptive research employs data collection techniques such as observation, interviews, and documentation. Data analysis involves three stages: data reduction, data presentation, and conclusion drawing. Data validity was ensured through triangulation techniques. The findings indicate: (1) To achieve high-quality education, Al Irsyad Al Islamiyyah 01 Elementary School applies an integrated, systematic, and comprehensive planning process through the following steps: (a) internal environmental analysis, focusing on school resources, including human, material, and technological assets; (b) external environmental analysis of geographical, socio-cultural, and economic factors; (c) appropriate strategy selection; and (d) comprehensive monitoring and evaluation. (2) In implementing programs to enhance educational quality, school leadership adopts policies such as: (a) continuous improvement of processes, (b) setting quality assurance and standards, (c) fostering a positive school culture, (d) organizational change, and (e) maintaining good relationships with stakeholders. (3) To ensure the success of educational quality programs, evaluations are conducted, including: (a) monitoring all activities from planning to implementation, (b) measuring individual and institutional performance, and (c) reporting on the implementation of all activities.